ILMU PENGETAHUAN DARI JOHN LOCKE KE AL-ATTAS - Izzatur Rusuli; Zakiul Fuady M. Daud (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
Knowledge is something that is very vital in human life, especially in building the civilization of a nation. This study focuses its analysis on how the concept of knowledge and its worldview both from the perspectives of the West and Islam. The results showed that knowledge in the West is a rational idea constructed by individuals based on the empirical experience. The characteristics of knowledge in the perspective of the West is a systematic, objective, general, reliable, and communal. Furthermore, Western knowledge derived from reason and the senses and therefore contributes to the truth that is both realism and idealism that Western knowledge of truth because truth is relative to current knowledge can be aborted by the truth of the knowledge that comes next if deemed no longer relevant. While knowledge in Islam are referred to as